PERANCANGAN WEB DESIGN DISTRO TANGKELEK - Dina Annisa; Zubaidah .; Syafwan . (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
AbstractDistro Tangkelek that is organized by young people is a company which produces T-shirt in Padang, had ever a website before, but it has been vacuumed because of lack of interest from audience toward the monotonous website. In the future, Distro Tangkelek has possibility to develop among its competitors. Based on this problem, it is needed to design Distro Tangkelek’s web to be more attractive, communicative and interactive used analysis that is SWOT analysis. Creative concept and program until final design are designed by considering visual communication aspect and design principles. The result of this design is a website consisting of 5 pages, supported by ten media in order to compare the website address Distro Tangkelek that is tangkelek.com.Kata kunci: desain, re-design, web design, distro, Distro Tangkelek